Catálogo de ressentimentos - Arrage Júnior, Samir Martins (2017)
There are two parts. The first one is fictional, and its title is Resentments' catalog. It is the story of a man collecting memories in order to write a book dedicated to his father, who had never read a literary work, not even a Master’s degree dissertation. The second one, Process catalog, presents a critical essay in which the Resentments' catalog genesis, inspirations, creative route and relations to another authors are introduced and debated. Intentionally, the two parts are close both in form and content, and that is why they have similar titles.